Vaccines for cancer interception in familial adenomatous polyposis - Johnson, David E.; Disis, Mary L. (Frontiers in Immunology, 2025)
Familial adenomatous polyposis (FAP) is an inherited autosomal dominant disorder caused by germline mutations in the adenomatous polyposis coli (APC) gene. FAP is associated with the development of hundreds of adenomas in the small and large intestines of individuals starting in the teenage years with a near 100% risk of developing colorectal cancer by adulthood. Eventually polyps develop throughout the gastrointestinal tract. Chemoprevention approaches have been somewhat successful in reducing polyp burden, but have not reduced the risk of the development of colorectal cancer or other cancers. The lack of efficacy of more standard drug approaches may be due to limited exposure to the agent only to specific periods while the drug is being metabolized, limited drug penetrance in the colon, and patient adherence to daily dosing and drug side effects. The success of immune therapy for the treatment of invasive cancer has led to research focused on the use of immune based approaches for polyp control in FAP, specifically polyp directed vaccines. Vaccines targeting antigens expressed in FAP lesions may be a superior method to control polyp burden and prevent disease progression as compared to classic chemoprevention drugs. A limited number of vaccines can be administered over a short period of time to generate a lasting immune response. Appropriately primed antigen specific T-cells can traffic to any site in the body where antigen is expressed, recognize, and eliminate the antigen expressing cell. Immunologic memory will allow the immune response to persist and the specificity of the immune response will limit toxicity to the targeted polyp. This review will examine the current state of vaccines directed against FAP lesions and highlight the challenges and opportunities of translating vaccines for cancer interception in FAP to the clinic.